THE REMEDY DEFICIT OF THE GRATK TREATY: RECONSTRUCTING PATENT REVOCATION FOR GENETIC RESOURCES IN INDONESIA - Moh. Amrullah; Dhaniar Budiastanti (Faculty of Law, Widya Gama University, Malang, 2026)
The WIPO Treaty on Intellectual Property, Genetic Resources and Associated Traditional Knowledge, adopted on 24 May 2024, is widely celebrated as a victory for the Global South after more than two decades of negotiation. This article interrogates that celebration. It argues that the Treaty embodies a remedy deficit: while it imposes a mandatory disclosure obligation on patent applicants, Article 5.3 prohibits Contracting Parties from revoking, invalidating, or rendering a patent unenforceable solely on the basis of a failure to disclose. Every landmark victory previously won by resource-holding states, from turmeric and neem in India to the brotowali dispute involving Indonesia, was secured through patent revocation rather than through procedural transparency. The Treaty therefore substitutes a strong remedy with a weak one. This study asks how patent revocation grounded in disclosure failure should be constructed within Indonesian law given that prohibition. Employing juridical-normative research with statutory, conceptual, and comparative approaches, it analyses Law Number 65 of 2024 on Patents, the Treaty text, and the revocation regimes of India, Brazil, and Switzerland. The study finds that the prohibition in Article 5.3 is narrower than commonly assumed because it is qualified by the word solely and by the freedom of implementation granted in Article 9.2. Indonesia may lawfully preserve revocation by routing disclosure information into the substantive examination of novelty and inventive step, and by treating deliberate concealment as a species of bad faith. The article proposes a three-tier remedy architecture and argues that ratification without prior reconstruction of Articles 130 and 132 of the Patent Law would leave Indonesia with a transparency obligation unaccompanied by any enforceable consequence.